A CHRISTIAN FEMALE LEADERSHIP FRAMEWORK: AN INSIGHT FROM CHRISTIAN HIGHER EDUCATION IN INDONESIA - Elfi Elfi; Indrawan Indrawan; Patricia Patricia; Ade Andriani Renouw (Universitas Pelita Harapan, 2023)
AbstractThere are only a few Christian- and Catholic-based universities in Indonesia that have females at the highest leadership. This may seem to be promoting the patriarchy concept as allegedly endorsed by Christianity, that woman was created to be a helper to man and because of that, woman is inferior to man. However, the Bible also mentions several female leaders and defends the inclusive culture where men and women are working together for God’ Kingdom. It is reflected by the many women at the middle management level in Christian higher education in Indonesia. Yet, studies about female in the middle management in Indonesia’s Christian universities are still limited. To further understand the issue, this study employs the phenomenology approach of the qualitative research method. In-depth interviews with six participants from two Christian universities in Indonesia were conducted in two weeks. From the findings, the authors propose a framework involving three elements that shape the Christian Female Leadership. Bahasa Indonesia AbstrakDi universitas berbasis Kristen dan Katolik di Indonesia, hanya terdapat sedikit wanita yang menduduki jabatan sebagai pimpinan tertinggi. Hal ini seakan mengesankan bahwa Kekristenan mendukung konsep patriarki di mana wanita di ciptakan sebagai penolong bagi pria yang karenanya, wanita dianggap berada di bawah pria. Namun, Alkitab sebenarnya juga menyebutkan beberapa pemimpin wanita dan membela budaya inklusif di mana wanita dan pria bekerja sama untuk Kerajaan Allah. Ini tercermin dari banyaknya wanita pada level manajemen menengah di pendidikan tinggi Kristen di Indonesia. Akan tetapi, studi tentang wanita sebagai pemimpin pada level madya pada kampus Kristen di Indonesia masih terbatas. Untuk memahami lebih lanjut tentang hal ini, penelitian ini menggunakan pendekatan fenomenologi dari metode kualitatif. Wawancara mendalam dilakukan dengan enam partisipan dari dua kampus Kristen di Indonesia dalam waktu dua minggu. Dari hasil penelitian, para peneliti mengusulkan kerangka pemikiran di mana terdapat tiga elemen yang membentuk Kepemimpinan Wanita Kristen.